2018
DOI: 10.1002/chem.201800892
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Synthesis of Drug Metabolites in Batch and Continuous‐Flow Reactors

Abstract: A medium-throughput screening (MTS) of biomimetic drug metabolite synthesis is developed by using an iron porphyrin catalyst. The microplate method, in combination with HPLC-MS analysis, was shown to be a useful tool for process development and parameter optimization in the production of targeted metabolites and/or oxidation products of forty-three different drug substances. In the case of the biomimetic oxidation of amiodarone, the high quantity and purity of the isolated products enabled detailed HRMS and NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…This strategy was later developed into a general method for the direct synthesis of opioid medicines with direct functionalization of oxazolidine intermediates without the oxazolidine hydrolysis step [ 100 ]. Besides the application of the iron-catalyzed reaction for the synthesis of pharmaceutical intermediates, it has also been used for the synthesis of drug metabolites [ 101 , 102 ]. For example, Singh et al [ 101 ] used an FeSO 4 -mediated N -demethylation strategy for the synthesis of the N -demethylated metabolite of cyamemazine 89a , a neuroleptic drug.…”
Section: Transition-metal Catalyzed N -Dealkylationmentioning
confidence: 99%
“…This strategy was later developed into a general method for the direct synthesis of opioid medicines with direct functionalization of oxazolidine intermediates without the oxazolidine hydrolysis step [ 100 ]. Besides the application of the iron-catalyzed reaction for the synthesis of pharmaceutical intermediates, it has also been used for the synthesis of drug metabolites [ 101 , 102 ]. For example, Singh et al [ 101 ] used an FeSO 4 -mediated N -demethylation strategy for the synthesis of the N -demethylated metabolite of cyamemazine 89a , a neuroleptic drug.…”
Section: Transition-metal Catalyzed N -Dealkylationmentioning
confidence: 99%
“…In the human body, the CP450-catalyzed oxidation of amiodarone produces N -deethyl-amiodarone ( 2 ) as the major human metabolite, however secondary deethylation resulting primary amine, mono and di-deiodinated, O -dealkylated and hydroxylated derivatives ( 12 ) have been also demonstrated at very low quantity [30,31,32]. In our recently published study, new derivatives were formed and identified in biomimetic oxidation [22]. The possible structures of metabolites ( 2 – 12 ) of amiodarone ( 1 ) were deduced from HRMS measurements (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This situation can be improved by immobilizing them on solid support by covalent binding or by secondary interactions like ionic bond [20,21]. In our recent work, we showed that meso-tetra(parasulphonato)iron porphyrin could be immobilized on aminopropyl group-modified silica by ionic bond, and the bonded catalyst could be applied in packed bed reactor to perform biomimetic oxidations under continuous flow conditions providing metabolites of antiarrhythmic drug, amiodarone [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, more than providing a remarkable toolkit for solving synthetic chemical challenges, biomimetic oxidative chemistry also offers a platform to study the oxidative metabolism of drugs . Such approaches require the best possible models of selected metabolizing oxidase enzymes.…”
Section: Biological Significance Of Rons Scavenging‐related Antioxidamentioning
confidence: 99%